2015
DOI: 10.1007/s12541-015-0070-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nip force on ink transfer in high resolution roll-to-roll printing

Abstract: In this paper, the effect of the nip force on the ink transfer in gravure printings was investigated. An adhesive force-based ink transfer model was suggested. This model is a function of the contact length between the ink and the substrate. The static simulation of the elastic deformation of the substrate was implemented under different nip forces. The simulation showed that the contact length (L IS ) was increased as the nip force increased. Accordingly, the ink transfer ratio was increased as the nip force … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…Obviously, this situation requires a compromise in line dimensions and overall conductance, which can be shifted toward smaller structures only by increasing the specific conductivity. Three studies dedicated to the line width optimization and the ink transfer for the R2R gravure printing of silver nanoparticle inks on PET film have been published by Nguyen et al At line speeds of 2–10 m min −1 , the authors obtained lines as narrow as 21 μm and demonstrated that air nip pressure and ink viscosity were the factors determining the line width, whereas for the height of the printed structures, the inks viscosity alone was dominant. Too high conductive structures, however, are not preferred in many cases, because coverage over a steep step can disturb the uniform and continuous deposition of subsequent functional layers, be it from solution or by dry techniques.…”
Section: Printed Circuitry and Electric Connectionsmentioning
confidence: 99%
“…Obviously, this situation requires a compromise in line dimensions and overall conductance, which can be shifted toward smaller structures only by increasing the specific conductivity. Three studies dedicated to the line width optimization and the ink transfer for the R2R gravure printing of silver nanoparticle inks on PET film have been published by Nguyen et al At line speeds of 2–10 m min −1 , the authors obtained lines as narrow as 21 μm and demonstrated that air nip pressure and ink viscosity were the factors determining the line width, whereas for the height of the printed structures, the inks viscosity alone was dominant. Too high conductive structures, however, are not preferred in many cases, because coverage over a steep step can disturb the uniform and continuous deposition of subsequent functional layers, be it from solution or by dry techniques.…”
Section: Printed Circuitry and Electric Connectionsmentioning
confidence: 99%
“…If F IS and F I are larger than F IC , the ink filled in the engraved cell is completely transferred to the web [22]. F IS is proportional to the product of the work of adhesive forces at the interface between the ink and web (W IS ) and the contact length between the web and ink (L IS ) [15]. If the nip pressure increases, L IS is increased, as shown in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Gravure printing is a good candidate for making conductive patterns in the R2R process because of the long life of its printing roll and its high compatibility with the R2R process [13]. However, the behavior of ink in the printing phase is more complex than that of inkjet printing, spray, and slot-die coating, and several printing factors such as web speed and nip pressure have a major interactive effect on the printing quality, which significantly affects the performance of electronic devices such as thin film transistors and flexible capacitors [14][15][16]. Several research groups have attempted to improve printing quality and resolution.…”
Section: Introductionmentioning
confidence: 99%
“…44 Meanwhile, a more traditional rollto-roll system reached a linewidth of 20 μm by adjusting the force applied between the rollers involved in ink application. 45 We characterized the IR heating profiles for each power input in relation to overall microheater performance of the two microheater designs used in subsequent application-based experiments (Fig. S4 †).…”
Section: Printed Microheater Characterization and Design Analysismentioning
confidence: 99%